1996
DOI: 10.2165/00003088-199630040-00001
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacokinetics of Zidovudine

Abstract: The battle against the acquired immune deficiency syndrome (AIDS) is now into its second decade, and substantial advancements have been made in our understanding of the complex life cycle of, and the immunopathology associated with, human immunodeficiency virus (HIV) infection, as well as of the drugs used to modify the course of disease. Zidovudine was the first agent approved for treatment of HIV disease, and since its widespread availability in 1987 the pharmacokinetic disposition and clinical effects of zi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
5

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 47 publications
(12 reference statements)
0
51
0
5
Order By: Relevance
“…However, the population enzymology component of the model was limited by the availability of only one data set each, describing the phosphorylation potential (V max ) for TK 1 and TMPK, respectively, in the PBM cells of infected subjects following ex vivo stimulation (48,49). These studies indicated substantial variances in the respective V max values between HIV-infected individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the population enzymology component of the model was limited by the availability of only one data set each, describing the phosphorylation potential (V max ) for TK 1 and TMPK, respectively, in the PBM cells of infected subjects following ex vivo stimulation (48,49). These studies indicated substantial variances in the respective V max values between HIV-infected individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Like other NRTI, ZDV undergoes three intracellular phosphorylation steps to form the active ZDV-5Ј-triphosphate (ZDV-TP), which inhibits wild-type HIV-1 RT with a median inhibitory concentration of about 0.035 M (72). The single-dose plasma pharmacokinetics of ZDV have been well described in HIV-1-infected individuals following intravenous and oral administration (1,10,20,34,65,78,90).…”
mentioning
confidence: 99%
“…It is also metabolised in the liver, mainly to the inactive glucuronide and is excreted in the urine as unchanged drug and metabolite. 7 Drug interactions have become an increasingly complex challenge for providers treating patients with HIV infection. Despite intense research in many areas of HIV infection, there is often a lack of formal drug interaction studies with HIV medications making providers to often rely on their own clinical judgment and to predict drug interactions without supporting data.…”
Section: A Survey Of 200 Individuals In 2004mentioning
confidence: 99%
“…The drug may theoretically show interactions with a large number of drugs which are also excreted through glucuronidation, like aspirin, NSAIDs, penicillins and oxazepam. Very limited data on the relevance of these possible interactions is available (95). The bioavailability of zidovudine may be decreased to a limited extent (22%) by simultaneouse intake with food (96).…”
Section: Zidovudinementioning
confidence: 99%